Pediatric Tenoten in therapy of childhood nocturnal enuresis - G. M. Dzhanumova; A. V. Budkevich; L. B. Ivanov (Неврология, нейропсихиатрия, психосоматика, 2010)
Objective: to study the efficacy of pediatric Tenoten in the treatment of secondary nocturnal enuresis in children. Subjects and methods. A comparative randomized study of the results of treatment was conducted in 36 children aged 5 to 15 years with secondary enuresis, who received pediatric Tenoten (n = 18; Group 1) and fenibut (n = 18; Group 2). Tenoten (pediatric formulation) was given a sublingual tablet thrice daily for 2 months. Therapeutic effectiveness was evaluated by clinical parameters (the number of nocturnal enuresis episodes per month and anxiety scale scores). Results. There was a significant reduction or complete cessation of nocturnal enuresis episodes in the majority of children and a decrease in anxiety levels. Positive clinical changes were accompanied by a trend toward normalization of spectral coherent EEG characteristics. Conclusion. Treatment with pediatric Tenoten results in a reduction in the rate of nocturnal enuresis episodes and, in some cases, in their cessation, positively affects the psychological status of children, and improves the indicators of brain bioelectrical activity. The drug causes no adverse reactions and is well tolerated.